First GLP-1 analog liraglutide: the result of clinical trails on efficacy - Alexander Sergeevich Ametov (Endocrinology Research Centre, 2011)
This review analytically considers the results of clinical trials on efficacy and safety and clinical perspectives of GLP-1 analog liraglutide